2019
DOI: 10.25259/jcis-9-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinicoradiological Spectrum of L-2-Hydroxy Glutaric Aciduria: Typical and Atypical Findings in an Indian Cohort

Abstract: Context: Neurometabolic disorders form an important group of potentially treatable diseases. It is important to recognize the clinical phenotype and characteristic imaging patterns to make an early diagnosis and initiate appropriate treatment. L-2-hydroxy glutaric aciduria (L2HGA) is a rare organic aciduria with a consistent and highly characteristic imaging pattern, which clinches the diagnosis in most cases. Aims: The study aims to describe the clinical profile, magnetic resonance imaging (MRI) patterns, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
0
11
1
6
Order By: Relevance
“…12 The mildly raised serum ceruloplasmin levels may be attributed to acute-phase reaction and raised urine copper due to renal derangement. Unlike previous case series in which all patients have been diagnosed with increased serum or urinary excretion of L-2HG, 4 8 9 our patients did not show abnormalities in the metabolic screening. Urinary excretion of L-2HG can be lower in patients with homozygous or compound heterozygous pathogenic missense variants than null variants, possibly due to residual enzyme activity.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…12 The mildly raised serum ceruloplasmin levels may be attributed to acute-phase reaction and raised urine copper due to renal derangement. Unlike previous case series in which all patients have been diagnosed with increased serum or urinary excretion of L-2HG, 4 8 9 our patients did not show abnormalities in the metabolic screening. Urinary excretion of L-2HG can be lower in patients with homozygous or compound heterozygous pathogenic missense variants than null variants, possibly due to residual enzyme activity.…”
Section: Discussioncontrasting
confidence: 97%
“…Imaging shows signal abnormalities in the dentate nucleus and cerebral white matter with characteristic sparing of subcortical white matter. 9 In this report, we present two patients with similar features of intellectual disability and seizures. Patients presented to us in the adolescent age.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The inception of L2HGA is also different, e.g., it might be either congenital with severe seizures and intellectual disability or might occur in middle age with mild features, which is an issue that may result in a delayed diagnosis of L2HGA [9][10][11]. Many studies have reported that elevated levels of L-2-hydroxyglutaric acid in the brain, probably linked with higher levels of lysine in the blood, may cause brain tumors [3,12,13].…”
Section: Introductionmentioning
confidence: 99%